Model Pembelajaran Student Teams Achievement Divission (STAD) Pada Pembelajaran Matematika di SMPN 46 Sijunjung - Yuli, Dwi; Eliza, Rivdya (Universitas Islam Negeri Imam Bonjol Padang, 2019)
This paper study about the interest and the low mathematics learning outcomes of eighth grade students of SMP N 46 Sijunjung in the school year 2017/2018. The aimsof this research are to know:1) the interest of student learning taught by the STAD cooperative learning model, 2) Mathematics learning outcomes from students that taught with the STAD type cooperative model in class VIII SMP N 46 Sijunjung 2017/2018 school year. This research is an experimental research and uses quantitative research methods. The subjects of this study were all eighth grade students of SMP N 46 Sijunjung. The sample taken by purposive sampling technique. The results showed that 1) the interest in mathematics learning of students taught with STAD was categorized as good with a percentage of 84.50% and 2) the mathematics learning outcomes of students taught with the STAD type cooperative model were higher than the mathematics learning outcomes of students taught with conventional learning models. It can be seen from the acquisition of the average value of the experimental class test 81.50 and the average value of the control class test 72.25. The percentage of student learning completeness in the experimental class was 70%, while in the control class 40%. After testing the hypothesis using the t-test, obtained t count> t table (2.68> 1.68) with αi = i0.05 at the 95% confidence interval, then the decision is H0 rejected and H1 accepted.